Simulation study of double layer Anti-Reflective Coating (ARC) in silicon solar cell by Ray Tracer - Mohammad, Nurul Nazwa; Mohd Fauzi, Nurfariena; Ahmad Nazri, Nurul Syahfina; Ghalip, Mumtazah Faqihah; Shamin, Nor Faranaz (2024)
The aim of this work is to investigate the effect of anti-reflection coating to improve the performance of silicon solar cells and to study double-layer ARC of various thicknesses on silicon solar cells. Four Light schemes with a double layer of ZnO/MgF2 with various thicknesses on 100 μm thin crystalline silicon (c-Si) were investigated. These parameters were manipulated by using wafer ray tracer in the PV Lighthouse simulator to study the efficiency of solar cells. The reflection, absorption, and transmission curve within the 300 - 1200 nm wavelength region were analyzed and the maximum potential photocurrent density (Jmax) for each light trapping (LT) scheme was calculated. It was found that with the addition of ARC into the c-Si, the Jmax increased to 34.06 mA/cm2 and obtained a 36.95% enhancement compared to the Jmax of the c-Si references (without ARC). Hence, it was observed that the double layer of ZnO/MgF2 ARC is significant to enhance the optimum broadband of light absorption.